PEMBUATAN IDENTITAS VISUAL WISATA AGRO LEMBAH KECUBUNG DESA PENANGGUNGAN TRAWAS MOJOKERTO: CREATING A VISUAL IDENTITY FOR THE WISATA AGRO LEMBAH KECUBUNG PENANGGUNGAN TRAWAS MOJOKERTO - Daffana Syahrul Ahsani; Diana Aqidatun Nisa (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Penanggungan Village is an area that has quite good potential in the tourism sector due to geographical location that in the highlands and has beautiful scenery view. Penanggungan village is famous as Brenjonk organic village and Wisata Agro Lembah Kecubung as a tourism icon.Wisata Agro Lembah Kecubung is just been formed and does not have strong branding so it has unable to attract lots of tourists, as a tourist village it is very important to have  a branding so that could attracts more tourists, for this reason a visual identity is needed as a design guide to make brand identity so that it attracts more tourists to visit, The visual identity designed is in a form of Brand Guide which includes logo design, supergraphics, mascots and merchandise.